Numerical Modeling of Structurally Controlled Ore Formation in Magmatic‐Hydrothermal Systems. (11th August 2022) - Codeço, Marta S.; Weis, Philipp; Andersen, Christine
Abstract: Faults and fractures can be permeable pathways for focused fluid flow in structurally controlled ore‐forming hydrothermal systems. However, quantifying their role in fluid flow on the scale of several kilometers with numerical models typically requires high‐resolution meshes. This study introduces a modified numerical representation of m‐scale fault zones using lower‐dimensional elements (here, one‐dimensional [1D] elements in a 2D domain) to resolve structurally controlled fluid flow with coarser mesh resolutions and apply the method to magmatic‐hydrothermal ore‐forming systems. We modeled horizontal and vertical structure‐controlled magmatic‐hydrothermal deposits to understand the role of permeability and structure connectivity on ore deposition. The simulation results of vertically extended porphyry copper systems show that ore deposition can occur along permeable vertical structures where ascending, overpressured magmatic fluids are cooled by downflowing ambient fluids. Structure permeability and fault location control the distribution of ore grades. In highly permeable structures, the mineralization can span up to 3 km vertically, resulting in heat‐pipe mechanisms that promote the ascent of a magmatic vapor phase to an overlying structurally controlled epithermal system. Simulations for the formation of subhorizontal vein‐type deposits suggest that the major control on fluid flow and metal deposition along horizontal structures is the absence of vertical structures above the injection location but their presence at greater distances. Using a dynamic permeability model mimicking crack‐seal mechanisms within the structures leads to a pulsating behavior of fracture‐controlled hydrothermal systems and prevents the inflow of ambient fluids under overpressured conditions. Plain Language Summary: Faults and fractures can serve as permeable pathways for focused fluid flow in the subsurface and therefore be essential geological features for the formation of economic mineral deposits. However, quantifying their role in the hydrothermal systems on the scale of several kilometers with numerical models typically requires high‐resolution meshes. This study presents a modified numerical representation of m‐scale fault zones with variable orientations to understand the hydrology of magmatic‐hydrothermal ore‐forming systems. The vertically extended systems simulation results show that ore deposition can occur along permeable vertical structures where ascending magmatic fluids are cooled by downflowing ambient fluids. Structure permeability and fault location can directly control the distribution of ore grades. In contrast, mineralization in horizontal structures requires the absence of vertical structures above the injection location of metal‐bearing magmatic volatiles but their presence at greater distances. Our model also shows how dynamic opening and closing of the structures in response to magmatic degassing can lead to a pulsating behavior and prevent the downflow of ambient fluids. Key Points: We describe structurally controlled fluid flow by representing faults and fractures as one‐dimensional line elements within a 2D modeling domain Vertical structures are efficient pathways for focused fluid flow and formation of high‐grade mineralization Ore formation in horizontal fractures requires a hydraulic connection to distal vertical fault zones